Improving Teaching and Learning in Higher Education Institutions: Is Discussion Method Theanswer? - Isaac Kofi Biney (MIER Journal of Educational Studies Trends and Practices, 2018)
This paper explores the role of discussion method in teaching for improving learning in higher education institutions. Teaching and learning are inseparable. However, teaching becomes effective only when it leads to meaningful learning. The lecture method for teaching dominates the classrooms in higher education institutions and is receiving negative comments from all stakeholders. Discussion method is considered superior by experts as it is more democratic by nature. It is inclusive, participatory and holds the key for empowering learners to be critical thinkers. A descriptive narrative design was employed for conducting the study. Qualitative techniques were employed at several stages throughout the study. Purposive and accidental sampling procedures were used. Semi-structured interviews guide were used for collecting data and ideas from the participants. It emerged that discussion method for teaching in classrooms possesses the power to stimulate quiet and shy-looking learners open up, think, participate and follow the instructions offered during discussions in the classrooms. It is recommended that the discussion method for teaching be employed because it creates an equal playing field for students to think critically and contribute to lessons.